Ecological and evolutionary significance of genomic GC content diversity in monocots - Šmarda, Petr; Bureš, Petr; Horová, Lucie; Leitch, Ilia J; Mucina, Ladislav; Pacini, Ettore; Tichý, Lubomír; Grulich, Vít; Rotreklová, Olga (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Genomic DNA base composition (GC content) is predicted to significantly affect genome functioning and species ecology. Although several hypotheses have been put forward to address the biological impact of GC content variation in microbial and vertebrate organisms, the biological significance of GC content diversity in plants remains unclear because of a lack of sufficiently robust genomic data. Using flow cytometry, we report genomic GC contents for 239 species representing 70 of 78 monocot families and compare them with genomic characters, a suite of life history traits and climatic niche data using phylogeny-based statistics. GC content of monocots varied between 33.6% and 48.9%, with several groups exceeding the GC content known for any other vascular plant group, highlighting their unusual genome architecture and organization. GC content showed a quadratic relationship with genome size, with the decreases in GC content in larger genomes possibly being a consequence of the higher biochemical costs of GC base synthesis. Dramatic decreases in GC content were observed in species with holocentric chromosomes, whereas increased GC content was documented in species able to grow in seasonally cold and/or dry climates, possibly indicating an advantage of GC-rich DNA during cell freezing and desiccation. We also show that genomic adaptations associated with changing GC content might have played a significant role in the evolution of the Earth's contemporary biota, such as the rise of grass-dominated biomes during the mid-Tertiary. One of the major selective advantages of GC-rich DNA is hypothesized to be facilitating more complex gene regulation.
Keywords: molekulární evoluce; plant genome; aklimatizace; DNA, Plant; Phylogeny; phylogenetic regression; Chromosomes, Plant; Magnoliopsida; genome size evolution; lipnicovité; Ecosystem; Evolution, Molecular; zastoupení bazí; Acclimatization; Base Composition; Genome, Plant; genetická variace; Genetic Variation; geographical stratification; fylogeneze; DNA rostlinná; Poaceae; chromozomy rostlin; genom rostlinný; ekosystém